Associations of risk perception of COVID-19 with emotion and mental health during the pandemic. - Han, Qing; Zheng, Bang; Agostini, Maximilian; Belanger, Jocelyn J; Gutzkow, Ben; Kreienkamp, Jannis; Reitsema, Anne Margit; van Breen, Jolien A; Collaborations, PsyCorona; Leander, N. Pontus; Abdul Khaiyom, Jamilah Hanum (Elsevier, 2021)
Background: Although there are increasing concerns on mental health consequences of the COVID-19 pandemic, no large-scale population-based studies have examined the associations of risk perception of COVID-19 with emotion and subsequent mental health.